How national culture on consumers' decision-making styles: a comparative study among Americans, Brazilians, Chinese, and japanese in the purchase of cell phones - Chan, Yie Leng (2009)
The influence of the national culture on consumer decision-making styles is investigated using a sample of Americans, Brazilians, Chinese, and Japanese consumers who have purchased a cell phone in the past three years. To make the research possible, a survey was used as a method of data collection. It relates Hofstede’s cultural classification typology with Sproles and Kendall’s consumer style inventory (CSI). The multivariate analysis of variance (MANOVA) results indicate six decision-making styles together with other consumer behavioral characteristics that can be used to distinguish and profile consumers who purchase cell phones. Empirical findings reveal that among Americans, Brazilians, and Japanese; Americans are the most quality conscious, brand conscious, innovative, and hedonistic shoppers; Brazilians are the most loyal, and Japanese, the most confused by overchoice consumers. Conceptual contributions and managerial implications are discussed.